Analysis of the students enterprise development of Al-Miftah Putri Vocational School through the business center program - Harizah, Siti (NUsantara Islamic Economic Journal, 2024)
Al-Miftah Vocational School has a responsibility towards its students to always inspire and motivate them to form a high mindset in entrepreneurship as a manifestation of the application of the learning process that has been undertaken while in the vocational-based school environment in which they are involved. With this goal in mind, the school took the initiative to build a group that would become a forum for exploring the talents and knowledge possessed by female students in the form of business work offering printing and convection businesses. The aim of this research is to determine the talent interest of Al-Miftah Vocational School female students in the business built by the school in order to produce female students who conform to the school's vision, namely creating a competent entrepreneurial mindset. The method in this research is descriptive qualitative with an approach using in-depth interviews and field observations. After more than 5 months of operating in a program called the Business Center, Al-Miftah Putri Vocational School was able to attract consumer interest little by little so that they began to receive orders for the services offered, the management of which was handed over to the female students directly, the school still played a role in it as a trainer, counselor, advisor, and business supervisor.